2000
DOI: 10.1080/10715760000300011
|View full text |Cite
|
Sign up to set email alerts
|

A chemiluminescense-based assay for S-nitrosoalbumin and other plasma S-nitrosothiols

Abstract: The lack of a simple assay for the quantification of S-nitrosothiols in complex biological matrices has hampered our understanding of their contribution to normal physiology and pathophysiological states. In this paper we describe an assay based upon the release of nitric oxide by reaction with a mixture consisting of Cu(I), iodine and iodide with subsequent quantification by chemiluminescense. With this method we can detect levels of S-nitrosothiols down to 5 nM in plasma. Following alkylation of free thiols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 21 publications
3
107
1
Order By: Relevance
“…The disadvantage of this method for the determination of nitrite is that it measures both nitrite and S-nitrosothiols. Marley et al [31] measured plasma RSNOs using Cu(1)/ KI/I 2 reagents after removing the nitrite with acidified sulfanilamide, which forms a diazonium complex that does not generate a chemiluminescence signal. Subsequent studies [32] have shown that the I 3 -reductive chemiluminescence assay also releases NO from RNNOs of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of this method for the determination of nitrite is that it measures both nitrite and S-nitrosothiols. Marley et al [31] measured plasma RSNOs using Cu(1)/ KI/I 2 reagents after removing the nitrite with acidified sulfanilamide, which forms a diazonium complex that does not generate a chemiluminescence signal. Subsequent studies [32] have shown that the I 3 -reductive chemiluminescence assay also releases NO from RNNOs of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…As a candidate for creating such a NO traffic protein, we selected human serum albumin (HSA), because HSA has high biocompatibility and good biodegradability, and because 'endogenous' S-nitrosothiols in serum are largely related to HSA. 13,14) Endogenous HSA has one Snitrosated site at Cys-34 thiol. The endogenous S-nitrosated HSA (SNO-HSA) was named 'Mono-SNO-HSA,' which has significantly superior stability compared with low molecular weight (LMW) S-nitrosothiols.…”
Section: Human Serum Albumin As the Key Play-er In The Nitric Oxide Tmentioning
confidence: 99%
“…The NOx content in plasma and tissues was determined on calibration curves prepared by adding known amounts of sodium nitrate to blank plasma or tissue homogenates in the concentration range 0.5-100 AM and expressed as AM and nmoles/g wet tissue respectively. RS-NO were determined by a copper(I)/iodide/iodine-mediated cleavage of RS-NO to form NO (Marley et al, 2000), which was quantified by its chemiluminescent reaction in gas phase with ozone. The reaction chamber containing 4 ml glacial acetic acid and 1 ml potassium iodide (50 mg/ml) was kept at 70 jC via a water jacket.…”
Section: Ozone-based Chemilumiscent Determination Of Plasma and Tissumentioning
confidence: 99%